The effect of continuous furnace load organization on temperature distribution during controlled atmosphere brazing process - Nadolny, Sławomir; Rogalewicz, Michał; Hamrol, Adam (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
Aluminum heat exchangers (AHEXs) represent a continuously evolving production sector with applications across various industries. Their mass production utilizes continuous furnaces combined with the controlled atmosphere brazing (CAB) process. The required heat is supplied through convection, conduction, and radiation. The degree of these interactions and their impact on the temperature achieved inside an AHEX can vary significantly depending on the type and mass of the load. The additional tooling, such as brazing jigs, also plays a crucial role. The design of these jigs, including their material and mass, is essential for the heat delivered inside an AHEX. The presence of brazing jigs can enhance conduction and radiation effects but may also reduce convection. Due to the use of different heating elements, varying lengths of continuous furnace chambers, and a nitrogen atmosphere control system, it is necessary to tailor the heating profile (furnace parameters) individually for each type of AHEX. The heating and cooling rates, as well as the duration in the elevated temperature, including the maximum temperature achieved inside an AHEX, are critical. This article presents a study on the impact of continuous furnace load organization (including load density and the presence of brazing jigs) on the temperatures achieved inside an AHEX.